2011
DOI: 10.1088/0004-637x/737/2/71
|View full text |Cite
|
Sign up to set email alerts
|

The BLUESHIFTING AND BALDWIN EFFECTS FOR THE [O III] Λ5007 EMISSION LINE IN TYPE 1 ACTIVE GALACTIC NUCLEI

Abstract: We use homogeneous samples of radio-quiet Seyfert 1 galaxies and QSOs selected from the Sloan Digital Sky Survey to investigate the connection between the velocity shift and the equivalent width (EW) of the [O III] λ5007 emission line, and their correlations with physical parameters of active galactic nuclei (AGNs). We find a significant and negative correlation between the EW of the core component, EW(core), and the blueshift of either the core (the peak), the wing, or the total profile of [O III] emission; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
99
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 61 publications
17
99
2
Order By: Relevance
“…While high-ionization narrow emission lines such as [O III] are not as blueshifted as high-ionization broad lines, they can have line peak shifts 18 of tens of km s −1 , with some extreme cases exceeding a hundred km s −1 (e.g., the so-called "blue outliers", Zamanov et al 2002;Boroson 2005;Komossa et al 2008;Marziani et al 2015). These average trends have been generally confirmed with recent large spectroscopic quasar samples (e.g., Vanden Berk et al 2001;Richards et al 2002;Shen et al 2007Shen et al , 2008Hewett & Wild 2010;Richards et al 2011;Shen et al 2011;Zhang et al 2011;Shen & Ho 2014), although differences in measuring the line center and the reference line used for systemic velocity will affect the exact value of the inferred velocity shifts.…”
mentioning
confidence: 67%
“…While high-ionization narrow emission lines such as [O III] are not as blueshifted as high-ionization broad lines, they can have line peak shifts 18 of tens of km s −1 , with some extreme cases exceeding a hundred km s −1 (e.g., the so-called "blue outliers", Zamanov et al 2002;Boroson 2005;Komossa et al 2008;Marziani et al 2015). These average trends have been generally confirmed with recent large spectroscopic quasar samples (e.g., Vanden Berk et al 2001;Richards et al 2002;Shen et al 2007Shen et al , 2008Hewett & Wild 2010;Richards et al 2011;Shen et al 2011;Zhang et al 2011;Shen & Ho 2014), although differences in measuring the line center and the reference line used for systemic velocity will affect the exact value of the inferred velocity shifts.…”
mentioning
confidence: 67%
“…Additionally, one extra Gaussian was adopted to model the blue wing of [O III] line (e.g., Komossa et al 2008;Zhang et al 2011 Osterbrock & Pogge 1987), then the flux ratio of the [S II] doublet is free in the fitting. The details of these components: broad components in green and narrow components in cyan, are shown in the panels of Figure 4.…”
Section: Balmer and Paschen Emission Linesmentioning
confidence: 99%
“…Only very recently spatially resolved optical, far infrared and mm spectroscopic studies convincingly showed evidences for the existence of such processes in the form of the predicted energetic outflows in ULIRGs with Seyfert nuclei in the local Universe (e.g. Feruglio et al 2010;Fischer et al 2010;Rupke & Veilleux 2011;Villar-Martín et al 2011;Rodríguez-Zaurín et al 2013;Zhang et al 2011;Westmoquette et al 2012;Rupke & Veilleux 2013;Harrison et al 2014;McElroy et al 2014; see also Elvis 2000 for a discussion on the ubiquitous presence of winds in the AGN structure).…”
Section: Introductionmentioning
confidence: 99%